Postoperative complications and outcomes of Mathieu and Snodgrass techniques in a sample of Iraq patients with anterior distal shaft hypospadias - Mohammad, Ehab Jasim; Hassan, Anas Falah; Khudhair, Mohammed Khalid; Abd, Ali Hussein (International Surgery Journal, 2018)
Background: Hypospadias is a common congenital anomaly of the penis in which the urethra opens proximal to its normal position at the tip of the glans. The purpose of this study was to compare the outcomes of Mathieu and Snodgrass techniques in the repair of anterior distal shaft hypospadias. Methods: From October 2009 to November 2010, forty five patients with the ages ranged 1 to 12 years suffering from anterior distal shaft hypospadias, were assessed. Inclusion criteria were anterior distal shaft hypospadias, and exclusion criteria were association with chordee, circumcision, and surgical repair history. Twenty-five patients underwent surgical repair using Snodgrass technique and 20 patients using Mathieu technique. Surgery was performed by one single surgeon, acquainted with both techniques. Patients were examined 1 week, and 1 month after discharge. Data including duration of the surgery, stenting time and any kind of complications such as break down, meatal stenosis, and fistula formation were collected. Also, success rate was calculated for every single patient and accordingly, the two groups were compared. Results: Mean operative time were 74±26minutes for Mathieu group and106.11±23 for minutes in Snodgrass group (P<0.05). Stenting mean duration was 6.8±1.1 days, in Mathieu group and, 6.3±0.8 days in Snodgrass group (P>0.05). The rate of break down, meatal stenosis, and fistula formation were 10%, 0%, and 5% in Mathieu group and 4%, 8%, and 8% in Snodgrass group respectively (P>0.05). Success rate was 88% in Snodgrass group and 85% in Mathieu group (P>0.05). Conclusions: In spite of some reports about preference for Snodgrass technique, we concluded that both techniques are as acceptable and as effective as each other for hypospodias repairing, regardless of cosmetic outcomes; however, we need further studies and larger sample sizes to determine which is the superior technique.